Specific Gene Expression and Epigenetics 2014
DOI: 10.1201/b16680-7
|View full text |Cite
|
Sign up to set email alerts
|

Renal Kallikrein Excretion and Epigenetics in Human Acute Kidney Injury: Expression, Mechanisms and Consequences

Abstract: Bone is a complex connective tissue characterized by a calcified extracellular matrix. This mineralized matrix is constantly being formed and resorbed throughout life, allowing the bone to adapt to daily mechanical loads and maintain skeletal properties and composition. The imbalance between bone formation and bone resorption leads to changes in bone mass. This is the case of osteoporosis and osteoarthritis, two common skeletal disorders. While osteoporosis is characterized by a decreased bone mass and, conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This may have important implications for diseases such as osteoporosis that have slower progression compared to cancers, as there may be a greater likelihood of negative side effects. Understanding the role played by DNAm in osteoporosis not only has much potential to enhance lifestyle interventions, but also the development of novel osteoporotic drug treatment [9]. Furthermore, knowledge of these associations also has the potential to reduce the social gradient of osteoporotic fracture by enhancing the current evidence base regarding why interventions should be targeted toward socially disadvantaged individuals as the most at risk group.…”
Section: Future Clinical Utilitymentioning
confidence: 99%
See 2 more Smart Citations
“…This may have important implications for diseases such as osteoporosis that have slower progression compared to cancers, as there may be a greater likelihood of negative side effects. Understanding the role played by DNAm in osteoporosis not only has much potential to enhance lifestyle interventions, but also the development of novel osteoporotic drug treatment [9]. Furthermore, knowledge of these associations also has the potential to reduce the social gradient of osteoporotic fracture by enhancing the current evidence base regarding why interventions should be targeted toward socially disadvantaged individuals as the most at risk group.…”
Section: Future Clinical Utilitymentioning
confidence: 99%
“…To advance understanding of the aetiology and pathogenesis of osteoporosis, there are now large-scale efforts to identify genes associated with fracture risk via genome-wide association studies (GWAS) of BMD [5][6][7][8]. The maintenance of BMD is not static, rather osteoblast and osteoclast differentiation processes are highly organized and driven by modifications in gene expression patterns throughout the life course [9]. Indeed, it is argued that the risk of developing osteoporosis occurs over the life course, with potential mechanisms involving epigenetic processes [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that DNA methylation at various genes, including cyclin‐dependent kinases such as CDKN2A , plays a role in skeletal development, homeostasis, and bone cell activity. Thus methylation has been implicated in mechanisms of osteoblastic differentiation and osteoclastogenesis, together with the transition from osteoblast to osteocyte . These experimental findings are complemented by data from genome‐wide methylation profiling studies in older patients, demonstrating differential methylation at genes such as the cyclin‐dependent kinase inhibitor CKDN1C and cyclin‐dependent kinase CDK20 is associated with BMD .…”
Section: Introductionmentioning
confidence: 89%
“…Epigenetic mechanisms are potential therapeutic targets due to their reversible nature. Several studies have suggested that methylome changes play an important role in osteoblast differentiation and activity (27)(28)(29)(30). Hypomethylation of the promoters of the runt-related transcription factor-2 (Runx-2), bone gamma-carboxyglutamate protein (Bglap, the coding gene for osteocalcin) and osterix (Osx) genes is involved in osteogenic differentiation of adiposederived mesenchymal stromal cells (MSCs) (31).…”
Section: Introductionmentioning
confidence: 99%